Tissue Engineering and Regenerative Nanomedicine - Reis, Rui L. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
[This book focus on the most recent advances related to the design and processing methods of different nanobiomaterials, films, and fibers; surface functionalization strategies, including biological performance assessment and cytocompatibility; and their applications in tissue engineering strategies.]